Object‐Oriented Lumped‐Parameter Modeling of the Cardiovascular System for Physiological and Pathophysiological Conditions. Issue 3 (11th February 2021) - Rosalia, Luca; Ozturk, Caglar; Van Story, David; Horvath, Markus A.; Roche, Ellen T.
Abstract: In this work, a lumped‐parameter Windkessel model of the cardiovascular system that simulates biomechanical parameters of the human physiology is presented. The object‐oriented platform provided by the MATLAB‐based modeling environment SIMSCAPE is employed to compute blood pressures and flows in each heart chamber and at various sites of the vascular tree. The hydraulic domain allows the determination of cardiovascular hemodynamics intuitively from geometrical and mechanical properties of the system, while custom elements model the pumping action of the heart and the effects of respiration on blood flow. The model is validated by comparing predicted hemodynamics with normal physiology during both systole and diastole, demonstrating that changes in arterial pressures with breathing are consistent with reported physiological effects of cardiorespiratory coupling. The capabilities of this platform are explored through two exemplary case studies: i) pressure‐overload heart failure due to aortic constriction, validated in vitro and via finite element analysis, and ii) single‐ventricle Fontan physiology, validated in vitro and compared with the clinical literature. This platform provides a practical tool for the calculation of cardiovascular hemodynamics from hydraulic parameters, enabling the intuitive creation of in silico representations of complex circulatory loops, the planning and optimization of medical interventions, and the prediction of clinically relevant patient‐specific hemodynamics. Abstract : A lumped‐parameter model of the cardiovascular system is developed to determine cardiovascular hemodynamics from hydraulic parameters in physiological and pathophysiological conditions, including left ventricular pressure overload and single‐ventricle physiology. This provides a practical tool for the simulation of complex circulatory loops, the optimization of medical interventions, and the prediction of patient‐specific hemodynamics of clinical relevance.